ANALISIS PENGARUH MOTIVASI KONSUMEN, PERSEPSI KUALITAS, SIKAP KONSUMAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING (Studi Pada Calon Konsumen Mobil Datsun di Kota Semarang) - Hanif, Muhammad; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2018)
This study aims to analyze the effect of consumer motivation, perceived quality, consumer attitudes and brand image on purchasing decisions with buying interest as an intervening variable. The study was conducted on prospective customers from Datsun car products in Semarang City. The number of samples used in this study were 150 respondents. The method of data collection is done through a questionnaire. This study uses Structural Equation Modeling (SEM) analysis techniques using the AMOS 22.0 analysis tool. The model of this study has fulfilled the rules of Goodness of fit, including: Chi square (125,125), probability (0,124), RMSEA (0,33), CMIN / DF (1,159), TLI (0,979) and CFI (0,984). The results of this study indicate that consumer motivation has a positive and significant effect on buying interest, perceived quality has a positive and significant effect on buying interest, consumer attitudes negatively affect buying interest, brand image has a positive and significant effect on buying interest, and buying interest has a positive and significant influence towards purchasing decisions.